Urgensi Peran Ulama Dalam Ranah Politik - Muhadi, Muhadi (Al-aqidah | Jurnal Studi Islam, 2018)
In the life of society, people will always be in touch with other community groups. Thus, inevitably every individual human will be in touch with many interests, needs and ideologies that exist in society. Such conditions cause human life will not be separated from political affairs. In other words, every side of human life will be in touch with political affairs. Political struggle is closely related to the affairs of state administration or government. In the case of the state or government, politics should be used to realize the good of the people. No different from the clerics entering the political vortex of his role in politics has given a positive color in the national political scene, especially in fighting the Islamic Shari?ah in it. But it can not be denied, too, that his involvement has led to a negative excess for Islam it self.